2007
DOI: 10.1248/cpb.55.1528
|View full text |Cite
|
Sign up to set email alerts
|

Compositions of Royal Jelly II. Organic Acid Glycosides and Sterols of the Royal Jelly of Honeybees (Apis mellifera)

Abstract: Royal jelly is a secretion from the hypopharyngeal and mandibular glands of worker bees, and it is the exclusive food of the queen bee for the entire span of both her larval and adult lives. With regard to the constituents of this material, it contains remarkably high amounts of organic acids in the total lipid fraction.1) Many organic acids mainly consisting of 8 to 11 carbon atoms such as 10-hydroxy-2-decenoic 2,3) and 10-hydroxydecanoic acids have been isolated. Among them, a minor component, 9-hydroxy-2-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 19 publications
3
34
0
Order By: Relevance
“…In agreement with our results, Valiollahpoor et al (2016) has reported higher maturation rates of sheep oocytes when cultured in the presence of royal jelly at various concentrations. The positive effect of royal jelly in improving COC maturation could be due to the various active compounds like proteins, essential amino acids (cystine, lysine and arginine), sugars (fructose, glucose, and sucrose), vitamins (A, B5, C, D and E), and lipids (Howe et al, 1985;Boselli et al, 2003;Kodai et al, 2007;Tamura et al, 2009). An early study observed increased errors in chromosomal segregation due to high oxidative stress during IVM, which compromises oocyte developmental potential after IVF in mice (Tarin et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with our results, Valiollahpoor et al (2016) has reported higher maturation rates of sheep oocytes when cultured in the presence of royal jelly at various concentrations. The positive effect of royal jelly in improving COC maturation could be due to the various active compounds like proteins, essential amino acids (cystine, lysine and arginine), sugars (fructose, glucose, and sucrose), vitamins (A, B5, C, D and E), and lipids (Howe et al, 1985;Boselli et al, 2003;Kodai et al, 2007;Tamura et al, 2009). An early study observed increased errors in chromosomal segregation due to high oxidative stress during IVM, which compromises oocyte developmental potential after IVF in mice (Tarin et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…2018 125 feed the queen honeybee throughout the larval period (Viuda-Martos et al, 2008;Isidorova et al, 2009). It contains the following: water (50-60%), proteins (18%), carbohydrates (15%), lipids (3-6%), mineral salts (1.5%), and vitamins, in addition to various bioactive substances (Howe et al, 1985;Boselli et al, 2003;Nagai and Inoue 2004;Kodai et al, 2007;Tamura et al, 2009). The antioxidative capacity of royal jelly was shown to be effective in protecting female and male gametes (Guo et al, 2009) and cryopreserved semen (Moradi et al, 2013;Shahzad et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 90% of lipids is constituted by fatty acids; the rest are neutral lipids, steroids, hydrocarbons and phenols (Nabas et al, 2014;Ramadan and Al-Ghamdi, 2012). The fatty acids of RJ have 8-10 carbon atoms, usually either hydroxy fatty acids or dicarboxylic acids, unlike organic acids of most animal and plant materials (Kodai et al,2007;Noda et al,2005;Ramadan and Al-Ghamdi, 2012). The analysis of the lipid components can be a criterion of the genuineness of the RJ, because an adulteration with honey or sugars, decrease the protein and lipid component, increase the concentration of minor sugars and makes RJ insoluble in alkaline medium (Boselli et al, 2003;Lercker et al,1981;Li and Chen, 2003).…”
Section: 2 Proteinsmentioning
confidence: 99%
“…PFL-4 and PFL-10 were identified as mandelic acid b-D-glucopyranoside [27] and its methyl ester [27], respectively. PFL-11 was identified as 10-hydroxydecanoic acid 10-O-b-D-glucopyranoside [28].…”
Section: Resultsmentioning
confidence: 99%